FUNGSI INFORMASI PRODUK DAN PENGETAHUAN PERAWATAN BAGI PEMAKAI LENSA KONTAK LUNAK DI OPTIK KOTA PADANG - Amir, Amril; Yusfita, Ermi; Saunir, Ihsan (Ensiklopedia of Journal, 2022)
This study discusses the function of product information and care knowledge for users of soft contact lenses in optics, Padang Padang City. This study aims to determine: (1) Information obtained by users on products available at Optik Padang City. (2) How to use and care for good soft contact lenses for eye health at Optik Padang City. (3) The impact of wearing and maintaining soft contact lenses on eye health at Optik Padang City. (4) Handling of the use and maintenance of soft contact lenses at Optik Padang City using quantitative descriptive methods. By using descriptive quantitative method. The population in this study were all patients wearing soft contact lenses at Optik Padang City in the period 15 December 2021-15 January 2022. Data were collected through questionnaires and research instruments using a Check List. The results showed that the respondents did not fully know the correct and correct information on soft contact lens care products, as many as 33 respondents (72%) studied the correct information on the correct soft contact lens care procedures from the product information provided. In addition, 27 (60%) respondents know how to use and care for soft contact lenses that are good for eye health at Optik Padang City, while 34 respondents (76%) know about the impact of wearing and maintaining soft contact lenses that are not according to the standard and 31 respondents (69%) did not know how to handle the use of soft contact lenses.